Pembentukan Manhaj Jamaah Dalam Pengembangan Masyarakat Islam - Dianto, S.Sos.I., M.Kom.I, Icol (Fakultas Dakwah dan Ilmu Komunikasi, 2019)
AbstractIslam as the religion of rahmatanlil'alamin means that Islam is universal and flexible to all aspects of life, including the life of mankind. Da'wah of Islam touches on the development of the resources of the Muslim community and the global community in humanizing humans, achieving a decent standard of living materially and immaterial (hasanah fid-dunya wal akhirat). However, the availability of potential natural resources has not been maximally utilized because of the low capacity and weak work ethic. Therefore, the establishment of Manhaj Jama'ah in development and empowerment activities is important to implement. Development that is centered on pilgrims can have a broader impact in efforts to build people's welfare and can build